Induction of the sporulation in Colletotrichum gloeosporioides penz, preserved under mineral oil - da Silva, Marilene Ferreira; Lima, Débora Maria Massa; Cavalcanti, Maria Auxiliadora (Pesquisa Agropecuaria Brasileira, 1991)
Studies were made with four unsporulated cultures of Colletotrichum gloeosporioides preserved under mineral oil during thirty-four to thirty-six years. Those cultures belonged to the collection of the "Mycotheca" of the Mycology Department of the Federal University of Pernambuco. To induce sporulation, leaves of papaya (Carica papaya L.) hydrated with mycelial suspension of the C. gloeosporioides and extract of leaves of papaya were used. After induction, sporulated cultures were obtained in the media potato-dextrose-agar (BDA) and oatmeal-mineral-salts-agar (ASMA-A). Most sporulation was observed in ASMA-A.
Keywords: Mycology; papaya leaves; culture media